Exploring the relation between technology and growth: The Spanish experience. - Ignacio Pomares; Rafael Aguado; Emilio Congregado (European Regional Science Association (ERSA), 1998)
The New Growth Theory has put the issue of endogenous technical change back into the center of attention. Although the statistical material available to the researcher wanting to investigate the economic influence of technological innovation is not very adequate, the aim of this paper is to analyse the impact of the technological change on long run growth in Spanish regions by means of the statistical analysis. Using a panel data for Spanish regions, we apply some econometric exercises to assess the significance of the relationship between technology and growth.
Keywords: 330